DINAMIKA AGRIBISNIS TEMBAKAU DALAM PEREKONOMIAN PROVINSI JAWA TIMUR - Rani Khairiyah; Rudi Wibowo; Jani Januar (UPT Penerbitan Universitas Jember, 2018)
This research aimed to know: 1) the role of tobacco agribusiness in terms of its relation with other economic sectors in economy of East Java, 2) the role of tobacco agribusiness seen from the economic impact it generates, based on multiplier effect on output, income, and employment in East Java. The research method used is descriptive and analytic method. Methods of data collection used documentation. Data analysis tools used are backward and forward linkage analysis and multiplier effect analysis. This research used Input-Output Table of East Java on 2010 and 2015 with classification of each 110 sectors aggregated into 20 sectors. The results of this research showed that: 1) during the period 2010-2015, the direct backward and forward linkage of tobacco agribusiness is low. Nevertheless, the value of cigarette industry and tobacco sectors in the future has increased, while the tobacco sector declines. While in the value of backward linkages, the tobacco industry and tobacco sector tends to increase, while the processed tobacco sector declines, 2) The role of tobacco agribusiness in creating output, income, and employment is high. However, on output and income multiplier, the processed tobacco sector shows declining value, while the tobacco and cigarette industry shows an increasing value, due to increased cigarette consumption in East Java. In labor multipliers, the tobacco sector has decreased, while the tobacco processing industry has increased.